Tlotok as a Cultural Pedagogical Space: Ethical and Moral Practices of the Tengger Community Based on the Telu Tok Concept - Putra, Muhammad Zanika Esa; Sukmawan, Sony (Journal of Language Intelligence and Culture, 2026)
Given the limited existing studies on the symbolic elements in the ritual practices of the Tengger community—particularly those related to ethical and moral values in everyday life—this study aims to examine (i) how the tlotok leaf reflects the ethical and moral values of the Tengger community; and (ii) how the tlotok leaf serves as a space for cultural pedagogy in the transmission of the sustainable ethical values of the Tengger community. This study employs a qualitative approach using Clifford Geertz’s interpretive ethnographic perspective. Research data were collected through observation and semi-structured interviews with traditional leaders. Data analysis was conducted through three main stages: (i) data reduction; (ii) data presentation; and (iii) conclusion drawing. The research findings reveal two key insights. First, the tlotok leaf embodies the ethics and moral values of the Tengger community through the concept of “telu tok,” reflected in the teachings of Tri Kaya Parisudha: thinking well, speaking well, and acting well. These principles manifest in the awareness of preserving nature, the practice of mindful speech, and acts of mutual cooperation in social life and the performance of traditional ceremonies.  Second, the practice of the tlotok leaf serves as a space for cultural pedagogy in the transmission of the Tengger community’s values of sustainable ethics. These values are learned through participation in social activities and rituals, thereby becoming embedded in everyday practices and passed down to subsequent generations. These findings suggest that cultural practices serve both as traditions and as mechanisms for the formation and transmission of ethical and moral values in the social life of the Tengger community.